Changes in bacterial diversity, co-occurrence pattern, and potential pathogens following digestate fertilization: Extending pathogen management to field for anaerobic digestion of livestock manure. (1st March 2023) - Gong, Jingyang; Liu, Baojun; Liu, Pingping; Zhang, Lina; Chen, Chen; Wei, Yuquan; Li, Ji; Ding, Guo-chun
Graphical abstract: Highlights: Potential pathogenic bacteria (PPB) succeed following digestate fertilization. Soil microbiome inhibits the resurgence of digestate-borne E. coli and Ent. faecium . PPB were prevalent in greenhouse soil organically or conventionally fertilized. Abstract: Digestate can spread pathogens into agroecosystem, posing serious threats to public health. However, the effect of digestate fertilization on digestate- or soil-borne pathogens has not been fully explored. Herein, two settings of microcosm experiment were performed with arable soil and digestate collected at two sites (Beilangzhong or Shunyi) to dissect the succession of the total and potential pathogenic bacterial communities following digestate fertilization. Each experimental setting consisted of three treatments, including digestate aerobically incubated in sterilized soil, and soil amended with sterilized or non-sterilized digestate. Digestate-borne potential pathogenic bacteria were enriched after the aerobic incubation, with Streptococcus sobrinus in the Beilangzhong setting, and Escherichia coli and Enterococcus faecium in the Shunyi setting. Potential soil-borne pathogenic bacteria, such as Acinetobacter lowffii and Pseudomonas fluorescens, were stimulated by the sterilized digestate in the Shunyi setting. Interestingly, S. sobrinus, E. coli, and Ent. faecium did not increase when digestate was amended into the non-sterilized soil, suggesting that soil microorganisms can inhibit the resurgence of these digestate-borne pathogens. A large-scale survey further revealed that organic fertilization exerted a site-dependent effect on different species of potential pathogen, but it did not enrich the total relative abundance of potential pathogenic bacteria in soils. Collectively, these results highlight that pathogen management of anaerobic digestion of livestock manure needs to be extended from anaerobic reactor to field.